The importance of the critical-reflexive portfolio in medicine graduation: An academic experience (Research, Society and Development, 2021)
Objective: This experience report aims to report the importance of the critical-reflective portfolio in the development of values, knowledge, skills and medical attitudes during medical graduation. Methodology: These are experiences lived from August 1, 2017 to June 30, 2019 by medical students from Faculdade ITPAC Palmas-TO during practical classes of the Integration Teaching Service Community module. From the first period, students are inserted in the Community Health Centers of the Municipality of Palmas in order to build theoretical and practical links related to the Unified Health System. At each weekly meeting, a portfolio page is produced with a narrative about the experience experienced and its critical-reflective analysis. At the end of the period, the students deliver the portfolios and receive a feedback from the tutor highlighting aspects of knowledge, skills and attitudes. Results and Discussion: The dynamics proposed by the critical-reflective portfolio allows academics to recognize the different health situations in their uniqueness, through thought and imagination. The exchanges of experiences reported provide students with understanding and judgment of situations, enabling the creation of perceptions, thoughts, values and improvement of medical skills and attitudes towards the patient and work team, supporting a humanized graduation. Conclusion: The construction of medical graduation using active teaching-learning methodologies, such as critical-reflective portfolios, contributes to the formation of values for action in the health field, such as critical reflection, empathy and creativity.